Contribution to the automation of the manufacturing process of cement tiles - Moumene, Keddani; Mohamed, Mostefai (IAES International Journal of Robotics and Automation (IJRA), 2020)
Automation is an important and necessary discipline in all industrial sectors. It facilitates the task of operators involved in any industrial installation. It allows the development of automated systems that perform dangerous, repetitive tasks and in environments hostile to humans. Automation of any production unit increases productivity and improves product quality. In this perspective, and within the framework of our end of studies project carried out within the University of Molay Tahar, our work consists The Automation Of The Manufacturing Process Of Cement Tiles in finding a concept and an order for the manufacture of a prototype intended the production of a cement tile production line by an s7 300 programmable controller.Â  Â